Integrasi Digital Twin Real-Time untuk Kendali Perangkat IoT di Lingkungan Smart Campus - Reza Putra Pradana; Afis Asryullah Pratama; Ahmad Fahriyannur Rosyady; Arvita Agus Kurniasari; Faisal Lutfi Afriansyah (Komunitas Dosen Indonesia, 2026)
The increasing demand for intelligent and sustainable energy management within higher education institutions has encouraged the adoption of IoT-based solutions; however, traditional IoT dashboards typically rely on text-based device lists and non-intuitive identifiers that lack spatial context. As a result, users often struggle to understand which physical devices they are controlling, leading to confusion, poor user experience, and a higher risk of operational errors when managing smart campus facilities. This study aims to develop and validate a Digital Twin–based Smart Campus system capable of synchronizing physical electronic devices with an interactive 3D virtual environment in real time, providing a spatially accurate digital representation of the lecturer room that mirrors the real-world layout. The research employs a systematic workflow that includes problem identification, literature analysis, installation of IoT devices such as Zigbee smart switches and ESP32 IR blasters, creation of a web-based Digital Twin interface, and development of optimized 3D room models using Blender. System testing was conducted to evaluate physical-to-digital and digital-to-physical synchronization performance, and FPS benchmarking was performed to assess usability across high-end, mid-range, and entry-level devices. The results show that the Digital Twin maintains 100% synchronization accuracy with millisecond-level response times and runs smoothly on diverse hardware. By enabling users to interact with devices directly through a virtual environment that visually matches the real room, the system reduces operational mistakes, improves user experience, and enhances awareness of energy usage. The study concludes that the proposed Digital Twin approach effectively overcomes key limitations of traditional IoT dashboards and offers a scalable, practical framework for Smart Campus implementations.